IMPLEMENTASI KEBIJAKAN REGISTRASI TENAGA KESEHATAN DI DINAS KESEHATAN PROVINSI SULAWESI TENGAH - Firmansyah, Andi Maman (Katalogis, 2015)
The purpose of research, to find out how the registration of health policy implementation in Central Sulawesi provincial health department and the factors that influence the policy. This study analyzed four factors that affect the implementation of policies according to the theory of George C. Edward III, namely: communication, resources, disposition, and Bureaucratic Structure. The method used is descriptive qualitative determination of informants snowball while a key informant was the section head bimdal registration and accreditation. Data collection techniques by observation, interviews, and documentation. The results showed all four factors in the analysis, 1) Communication in the bureaucracy as well as to the applicant has been pretty good. 2) Resources of facilities that are not adequately support the implementation of the policy influence. 3) Disposition of the policy implementers from honest attitude and commitment both indicated that pelaksan policy strongly supports the policy. 4) The bureaucratic structure is already quite good in terms of uniformity in the operation of the organization operationally because the implementers refers Permenkes.